Konstribusi Usaha Kue Apam Dalam Ekonomi Keluarga Pedagang Kue Apam di Kota Barabai - Fitriani, Adha; Marliani, Gusti (Scientific : Jurnal Ilmu-Ilmu Sosial dan Ekonomi, 2017)
The growth of household industry today is one alternative to improve the family economy. Their circumstances require them to participate in working to help the family economy to earn enough income just to survive. One way to earn extra income by trying to trade. The low level of education and skills that have made the cake traders prefer to work in the informal sector. By working in this sector they can divide the time between family and work done. Traders of cakes The majority of women who have characteristics such as individual characteristics and household characteristics that can affect the income contribution of women. Women's working roles have a relationship to women's income contribution to household income. The large or small amount of income received by working women will affect the increase in household income, and the income can be used for various things. This means that women's incomes contribute to their home economies.